(untitled) (Scientific journal of the Fergana State University, 2024)
This article is devoted to the study of teaching methods based on gaming technologies in the development of students’ speech competence in English. In today’s globalized world, mastering the English language is an important task. Since traditional teaching methods are insufficient to meet these needs, the need for new pedagogical approaches is increasing. This article analyzes how gaming technology can help students learn English in a fun and motivating environment. Game-based learning encourages students to practice speaking by testing their speaking skills in real-life situations. The article discusses strategies for integrating gaming technologies into education, their impact on the educational process and the effectiveness of learning. Theoretical and practical examples will show how game-based learning can make a difference in English language learning and how it can help students develop essential skills.